Keefektifan Pembelajaran dengan Menggunakan Pendekatan PBL dan CTL Ditinjau dari Kemampuan Pemecahan Masalah dan Motivasi Belajar - Husnul Laili (AS-SABIQUN, 2019)
This study aimed to describe: 1) the effectiveness of the PBL (Problem based Learning) and CTL (contekstual teaching and learning) in terms of students’ problem solving ability and motivation to learn mathematics; 2) the effectiveness of the PBL in comparison with the CTL type of cooperative learning in terms of students’ problem solving ability and motivation to learn mathematics. To find out the effectiveness of the PBL and CTL in each variable, the data were analyzed using one-sample t-test at a significance level of 5%. To compare the effectiveness of the PBL and CTL, the data were analyzed using multivariate T2 Hotelling with the significance level of 5% and followed up with the univariate analysis using a with criterion bon feroni. The results of the study show that: 1) the PBL and the CTL are effective in terms of students’ problem solving ability and motivation to learn mathematics.